Profile of aerobic capacity (VO₂ max) of student athletes: a comparative study based on gender and sports group - Huda Muhammad Kautsar; Angga M Syahid; Geraldi Novian (Jurnal Patriot, 2025)
Problems: Aerobic capacity (VO₂ Max) is a fundamental component of physical condition that supports athletic performance in various sports. Grouping sports based on their physiological characteristics, such as martial arts, games, and measurable sports, can help in analyzing athlete fitness profiles. Furthermore, established physiological differences between genders are known to significantly influence aerobic capacity. Purpose: This study aims to map the profile and analyze differences in aerobic capacity among student athletes based on gender and sports classification. Methods: This study used a descriptive-comparative design with 57 student-athletes (37 men, 20 women, aged 20.98 ± 0.6 years) from 18 sports at the Universitas Pendidikan Indonesia, selected using convenience sampling. Aerobic capacity data (VO₂ Max) were collected through the standard Multistage Fitness Test (MFT) instrument. Data analysis was performed using descriptive statistics, Independent Samples T-test, and One-Way ANOVA. Results: This study showed that male athletes had a significantly higher mean VO₂ Max (42.02 ± 5.14 ml/kg/min) than female athletes (30.91 ± 4.67 ml/kg/min). Further analysis of the male group found no significant differences in VO₂ Max between the Martial Arts (43.33 ± 4.09 ml/kg/min), Games (41.6 ± 4.87 ml/kg/min), and Measured (43.9 ± 3.12 ml/kg/min) groups. Similarly, in the female group, no significant differences were found between Martial Arts (31.5 ± 6.80 ml/kg/min), Games (30.0 ± 3.01 ml/kg/min), and Measured (37.7 ± 1.27 ml/kg/min). Conclusion: Gender is the most dominant differentiating factor for the aerobic capacity of student athletes in this study, while grouping based on sports clusters did not show significant differences. These findings indicate that the variation in athletic levels within each sport group is greater than the differences between sport groups themselves. Further research is recommended to conduct similar analyses by controlling for equivalent athletic levels to obtain a more specific picture of the physiological demands between sports.